Business failure and the dimension of entrepreneurial learning: study with entrepreneurs of micro and small-sized enterprises - Dias, Tania Regina Frota Vasconcellos; Martens, Cristina Dai Prá (Revista de Administração da UFSM, 2019)
From a dynamic learning perspective, the development of comprehensive entrepreneurship takes into account that entrepreneurs learn during the creation and management of their enterprises. This study aims to analyze the dimension of entrepreneurial learning of entrepreneurs of micro and small-size companies that had business failure and have created new businesses. The methodology consists in a qualitative and exploratory study, with cross-section approach and longitudinal perspective. Three entrepreneurs were selected to participate in the study based on convenience and availability. Data were collected through interview in depth, using a standard protocol. Content analysis was used having the narrative as a basis for the research. The results showed that all entrepreneurs, at the time that they had business failure, presented an immediate and spontaneous reflexive action because they did not remain inactive when facing the challenges that had led them to stop theirs activities. In consideration of the dimension of entrepreneurial learning, we suggest that the acquisition of knowledge related to the overcoming of adversities and obstacles is able to stimulate and enable entrepreneurs to create a new venture.